Arah pembangunan energi terbarukan di Indonesia pada era presiden Joko Widodo - Bosman, Ofan; Putra, Reza Dwi (Energy Justice, 2024)
Background: Indonesia has a large amount of renewable energy, but not very wide. This research aims to study the development of renewable energy under the leadership of Joko Widodo. Methods: They are qualitative methods using qualitative methods, conducted through literature analysis and literature research. Findings: President Joko Widodo announced a series of rules on renewable energy, namely the Minister of Energy and Natural Resources (ESDM). Revising the Ministry of Energy and Natural Resources (Kemen ESDM) regulations. The Ministry of Energy made provisions for renewable energy use in May 2018. This is the presidential decision 3912/2018 as amended by the Ministry of Energy and Resources regulations. A study on the implementation of physical activities in the fields of renewable energy use and energy conservation, September 17, 2017. Conclusion: On the 22nd, it was the National Energy Master Plan (RUEN). Some of these rules are based on national energy policy (KEN) and statutory numbers. It was published on June 30, 2006. Renewable energy development (RET) is one of the President's priorities to ensure the safety and sustainability of the country's energy. In this early stage, the Joko Widodo government has made considerable efforts to develop BSE while studying policies and implementation.